НАСТУПНІСТЬ У ФОРМУВАННІ УМІНЬ САМОСТІЙНОЇ НАВЧАЛЬНОЇ ДІЯЛЬНОСТІ СТУДЕНТІВ ПЕДАГОГІЧНОГО УНІВЕРСИТЕТУ НА ОРГАНІЗАЦІЙНОМУ, ОПЕРАЦІЙНОМУ І ПРЕДМЕТНОМУ РІВНІ (Педагогіка вищої та середньої школи, 2007)
The article deals with the problem concerning existing possibilities of pedagogical influence while forming students' self-directed educational activities skills in Pedagogical University on organizational, functional, and subjective levels.